Training of Production Managers for Machine-building Enterprises - I. A. Ivanov; G. E. Persiyanova (Высшее образование в России)
The article discusses the problem of a discrepancy between University programs of production managers training for industrial enterprises and the modern requirements to such specialists. The result is an acute shortage of qualified top managers and middle managers, whereas university graduates can’t find specialty related occupation.To assess the needs of machine-building industry in production managers and various professionals a study was conducted at Novocherkassk Electric Locomotive Plant, which is the largest machine-building enterprise in Russia for production of mainline freight and passenger electric locomotives. Based on the survey using a direct regression, the conclusion was drawn about the current need in specialists of the main and auxiliary shops of the plant. The study showed that approximately 65% of the required specialists with higher education are production managers.To solve the problem of production managers shortage, the authors have developed a training program for production managers who will be able to manage human resources and at the same time effectively use technical tools to perform production process. The implementation of this program will enhance productivity, competitive advantages of domestic manufacturing and graduates’ job placement.